Analisis Pemanfaatan Plastik Polystyrene (PS) senagai Bahan Tambahan Aspal AC-WC dan AC-BC dengan Metode Marshall - Andi - Sulfanita (JURNAL SIPIL SAINS, 2023)
ABSTRACT : Availability of Polystyrene (PS) type plastic waste in various surrounding environments, added to the hot asphalt mixture to improve road pavement performance. This study aims to determine the effect of adding Polystyrene (PS) plastic to the Marshall characteristics of AC-WC and AC-BC asphalt based on the 2018 General Highways Specifications. The test results on Marshall characteristics with a mixture of normal asphalt content of 5% and 6% obtained Optimum Asphalt Content (KAO) of 5.5% for each asphalt AC-WC and AC-BC. Marshall testing on AC-WC asphalt with polystyrene materials using 4% and 5% levels. Then the Stability, VMA, VIM, Flow, and Marshall Quotient values increase, while the VFA value decreases with each addition of Polystyrene (PS) content, this indicates the low density of the asphalt mixture against water and air. However, all variations in the levels of plastic additives on AC-WC asphalt met the specifications, while the Marshall test on AC-BC asphalt with polystyrene materials used levels of 4% and 5%. Then the Stability, VFA, Flow, and Marshall Quotient values have increased, while the VMA, and VIM values have decreased with each addition of Polystyrene (PS) content, this indicates that the voids in the aggregate and voids in the mixture are getting smaller, and causing the asphalt to not be able to fill the empty space too much. and aggregate binding. However, only the VIM value at 5% with a value of 2.58% does not meet the specifications between 3% -5%. So, apart from that, all the added ingredients of asphalt plastic AC-BC meet the specifications. Utilizing Polystyrene (PS) type plastic waste in hot asphalt mixtures can improve the quality of Marshall characteristics and can be used as an additive in asphalt flexible pavement.Â Keywordsi : AC-WC, AC-BC, Marshall, KAO, Polystyrene (PS).